1985
DOI: 10.1172/jci111920
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal sodium transport in synaptosomes from brain of uremic rats.

Abstract: The causes of central nervous system (CNS) dysfunction in uremia are not well known and are not completely reversed by dialysis. This problem was investigated in synaptosomes, which are membrane vesicles from synaptic junctions in the brain. We measured Na uptake under conditions of control, veratridine stimulation, and tetrodotoxin inhibition, in synaptosomes from normal and acutely uremic (blood urea nitrogen, 250 mg/dl) rats. In the control state, maximal Na uptake was 2.2±0.2 and 1.9±03 nmol/mg of protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 40 publications
3
28
0
Order By: Relevance
“…An assay of uptake in freshly prepared synaptosomes from rats with 48 h of hypernatremic dehydration demonstrated a 17% increase in Na+-specific taurine transport compared to synaptosomes isolated from control animals. The stability of synaptosomal taurine uptake in stored vesicles is in accord with previous work investigating cerebral ion transport in which frozen synaptosomes were used (12).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…An assay of uptake in freshly prepared synaptosomes from rats with 48 h of hypernatremic dehydration demonstrated a 17% increase in Na+-specific taurine transport compared to synaptosomes isolated from control animals. The stability of synaptosomal taurine uptake in stored vesicles is in accord with previous work investigating cerebral ion transport in which frozen synaptosomes were used (12).…”
Section: Resultssupporting
confidence: 81%
“…These features were virtually identical to those reported by Fraser et al (12). Thus, passive uptake into synaptosomes of varying size or transport by contaminating organelle membranes cannot account for the differences in taurine transport between hypernatremic and control animals.…”
Section: -Chd Chronic Hypernatremic Dehydrationsupporting
confidence: 87%
See 1 more Smart Citation
“…In a limited number of other tissues (9)(10)(11)(12), there is evidence that sodium pump activity may be abnormal in uremia, and in skeletal muscle of dialysis patients, there is an abnormally low resting membrane potential and increased intracellular sodium, consistent with a defect in sodium pump function (13). Despite these reports, it cannot be concluded that in uremia, all tissues will exhibit the same pathophysiology for defective basal and/or hormonally stimulated active sodium transport.…”
Section: Introductionmentioning
confidence: 99%
“…We observed abnormal extracellular amino acid neurotransmitter concentrations in the mediobasal hypothalamus of uremic rats, compatible with disturbed regulation of hypothalamic neurons by higher neuronal centers (6). The function of brain synaptosomes is altered in experimental uremia (7)(8)(9)(10). However, we also demonstrated direct inhibition of GnRH secretion from cultured hypothalamic neurons by a factor circulating in uremic serum (11).…”
mentioning
confidence: 99%